Animated machines, organic souls: Maturana and Aristotle on the nature of life - Álvarez-Vázquez, Javier Y. (Novelty Journals, 2016)
The emergence of mind is a central issue in cognitive philosophy. The main working assumption of the present paper is that several important insights in answering this question might be provided by the nature of life itself. It is in this line of thinking that this paper compares two major philosophical conceptualizations of the living in the history of theoretical biology, namely those of Maturana and Aristotle. The present paper shows how both thinkers describe the most fundamental properties of the living as autonomous sustenance. The paper also shows how these theoretical insights might have a consequence upon our understanding of a specific constructiveness of human cognition, here referred to as enarrativity, if this can be considered in a structural as well as evolutionary connection with the structure of life as such. The paper finally suggests that the structural connection made here can be traced from the fundamental organization of self-preservation to survival behaviors to constructive orientation and action.